HUBUNGAN KESEIMBANGAN DAN KOORDINASI MATA DAN KAKI DENGAN KETERAMPILAN SEPAK SILA PERMAINAN SEPAKTAKRAW PADA ATLET TAKRAW SMAN 1 SENTAJO RAYA - Fajri Yulhan; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observations and observations in the field of sepaktakraw team at SMAN 1 Sentajo Raya, there are several problems found in these observations, among them the authors observed that the players did not perform football silently during the cradle, received sharp service, fed the ball to the smasher, this was caused by a lack of balance, eye and foot coordination in performing football in the sepaktakraw game. While the training that has been given by the trainer is maximized. This research was conducted at the SMAN 1 Sentajo Raya School Field. Research included in the type of correlational research (Correlation Research) with the total population of the study amounted to 9 people SMAN 1 Sentajo Raya athletes. The data in this study are data on Balance Tests, Eye and Foot Coordination Tests and Sila Soccer Tests to see the correlation of these variables. Based on the results of research and data processing using statistical research procedures, it was concluded that for the relationship of X1 variables with Y variables obtained r_count = 0.9790> rtabel = 0.666, the relationship of variable X2 with Y variables obtained r_count = 0.9750> r_tabel = 0.666, relationship Y variable X1 and X2 obtained by r_count = 0.9837> r_tabel = 0.666 then there is a relationship between variables X1 and X2 with variable Y. Thus Ha can be said to be accepted. The conclusion of the hypothesis was accepted at a significant level of α = 0.05 in other words there was a significant relationship between balance, eye and foot coordination with soccer skills in the sepaktakraw team of SMAN 1 Sentajo Raya.Key Words: Balance, Coordination, Sepak Sila